Effect of Silibinin in Lowering the Intraocular Pressure in Normotensive Rabbits: Interaction with Betaxolol - A. Hussain, Saad; M. Mohammed, Haider; H. Jwaied, Ahmed; H. Abdulrazzaq, Munaf (Iraqi Journal of Pharmaceutical Sciences, 2017)
Previous reports demonstrated the effectiveness of silibinin hemisuccinate as a potential intraocular pressure-lowering agent. The exact mechanism by which silibinin exerted this effect has not yet been documented, but might suggested to interfere with aqueous humor formation. The present study was designed to evaluate the comparative efficacy of silibinin as IOP lowering agent to that of betaxolol in normotensive rabbits, and the interaction of silibinin with betaxolol as a way for investigating the possible mechanism of action of silibinin in this respect. The effects of instillation of 0.75% silibinin solution and 0.5% betaxolol eye drops in the eyes of normotensive rabbits were evaluated using indentation tonometry. The results showed that 0.75% solution of silibinin was more potent than betaxolol (0.5%) in lowering IOP in normotensive rabbits. Furthermore, the effect of pre- and post-instillation of silibinin-betaxolol combination showed a characteristic antagonistic feature. In conclusion, silibinin appears to be more potent than betaxolol in lowering IOP in normotensive rabbits; the pre- and post-instillation of silibinin provide experimental evidence for the possible antagonistic effect of betaxolol with the IOP-lowering effect of silibinin. Key words: silibinin, betaxolol, cAMP, PDE-inhibitors